Delivered growth factor therapy to improve healing after rotator cuff repair - Emilie V Cheung (Dove Medical Press, 2010)
Emilie V Cheung, Luz Silverio, Jeffrey YaoDepartment of Orthopedic Surgery, Stanford University, Redwood City, CA, USABackground: Degenerative rotator cuff tears are a significant cause of shoulder pain in the aging population. Rotator cuff repair surgery may be more successful when growth factors are delivered to the repair site. This study was designed to determine the cellular processes involved in normal bone-to-tendon healing and the current approaches used for biologic augmentation of rotator cuff repair.Methods: This review focuses on animal studies of rotator cuff repair and early human trials.Results: Regular bone-to-tendon healing forms a fibrous junction between tendon and bone that is markedly different from the original bone-to-tendon junction. Tendon augmentation with cellular components serves as scaffolding for endogenous fibroblastic cells and a possible source of growth factors and fibroblastic cells. Extracellular matrices provide a scaffold for incoming fibroblastic cells. However, research in extracellular matrices is not conclusive due to intermanufacturer variation and the lack of human subject research. Growth factors and platelet-rich plasma are established in other fields of research and show promise, but have not yet been rigorously tested in rotator cuff repair augmentation.Conclusions: Rotator cuff repair can benefit from biologic augmentation. However, research in this field is still young and has not yet demonstrated that the benefits in healing rates are significant enough to merit regular clinical use. Randomized controlled trials will elucidate the use of biologic augmentation in rotator cuff repairs.Keywords: rotator cuff, shoulder pain, growth factors, repair